Phytochemical screening, antibacterial and antioxidant activity of Ethanolic seed extract of Kadios (Cajanus cajan) from Igbaras, Iloilo, Philippines - Bautista, Lance Ruther E. (2016.)
Natural products are products which may have been chemically synthesized, through semi- or total synthesis. The presence of these natural sources gave us greater opportunity for discovery and different innovations, as answers to the emerging needs of the people. This study focused on the chemical properties, antibacterial and antioxidant activity, of Cajanus cajan, popularly known as Kadios, from Igbaras, Iloilo, Philippines. A total of 371.98 grams of air-dried C. cajan seeds was macerated to 1000 mL of ethanol for 72 hours. The concentrated extract was subjected to three tests and assays. All tests were done in triplicates. The test for phytochemicals, which served as the preliminary screening, revealed that the ethanolic extract of Kadios seeds contains alkaloids, flavonoids, phenols, saponins, tannins, quinones, and steroids. The antibacterial assay showed that the ethanolic seed extract of C. cajan can inhibit growth of Gram-negative bacteria, E. coli, with zone of inhibition equal to 10.3±2.15 mm to 33±1.63 mm. The antioxidant assay revealed that the extract has positive inhibition only at high concentration against DPPH, and so IC50 was further determined to be 27,310 µg/mL. Statistical analyses were also done, and confirmed that there is significant difference among the data at (P<0.05). Summing up, the extract has antibacterial activity and minimal or almost close to zero antioxidant activity, while containing a remarkable number of secondary metabolites causing the chemical activities of the extract.
Thesis (Bachelor of Science in Chemistry) University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Cajanus cajan (KadIos) -- Igbaras; Antibacterial; Antioxidant